Scheinwelten : Die Geschichte der Perspektive - Geyer, Bernhard (Leipzig : E.A. Seemann, 1994)
Lorenzetti, Ambrogio ; Giotto ; Raffael ; Robert, Hubert ; Pannuni, Giovanni Paolo ; van Steenwyck, Hendrick ; Gijsbrechts, Cornelis ; Pozzo, Andrea ; Backhuysen, Ludolf ; Bellotto, Bernardo ; Hobbema, Meindert al.
boek